Notes on the grasslands species between Iquitos and Nauta, Loreto, Peru - Tovar-Serpa, Oscar (2009)
During the year 2006 were collected species of the grassland near the road between Iquitos and Nauta. We identified 69 species. The vegetation that characterizes this region is tropical rainforest, where the lower stratum is occupied by pastures consisting mainly of true grasses (Poaceae) and small proportion of species from other families such as Fabaceae, Malvaceae, Acanthaceas, Amaranthaceas, etc. We present keys for the identifica- tion of families, genera and species.